2012
DOI: 10.7776/ask.2012.31.5.298
|View full text |Cite
|
Sign up to set email alerts
|

A Relationship of Tone, Consonant, and Speech Perception in Audiological Diagnosis

Abstract: This study was designed to examine the phoneme recognition errors of hearing-impaired (HI) listeners on a consonant-by-consonant basis, to show (1) how each HI ear perceives individual consonants differently and (2) how standard clinical measurements (i.e., using a tone and word) fail to predict these differences. Sixteen English consonant-vowel (CV) syllables of six signal-to-noise ratios in speech-weighted noise were presented at the most comfortable level for ears with mild-to-moderate sensorineural hearing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Experienced clinicians rarely agree on the answer to this question. Previous research has shown that hearing impaired listeners will not have the same speech perception ability even though they may have the same pure tone threshold and configuration [ 7 8 9 10 ]. In a series of studies by Han and Allen [ 8 ], No and Lee [ 9 ], hearing impaired subjects with symmetrical sensorineural hearing loss showed different consonant perception ability within and/or across multiple subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experienced clinicians rarely agree on the answer to this question. Previous research has shown that hearing impaired listeners will not have the same speech perception ability even though they may have the same pure tone threshold and configuration [ 7 8 9 10 ]. In a series of studies by Han and Allen [ 8 ], No and Lee [ 9 ], hearing impaired subjects with symmetrical sensorineural hearing loss showed different consonant perception ability within and/or across multiple subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Baddeley [ 10 ] supported this statement in that the configuration of hearing loss had a limitation in terms of predicting speech perceptual errors. Under a simulation technique of HA amplification, 20 hearing impaired subjects with symmetrical pure-tone audibility did not receive the same benefit from both ears [ 7 ]. Thus, limited information provided by current average correct response did not include the specific features of speech perception in these hearing impaired listeners.…”
Section: Introductionmentioning
confidence: 99%